Circular Economy Adoption by European Small and medium-sized enterprises: Influence on Firm Performance - Rosa, Bruna Oliveira (2023)
Purpose – This study aims to analyze the elements that influence the adoption of Circular Economy activities by European small and medium enterprises (SMEs) and how these activities affect firm performance, following a multi-level approach. Theoretical framework – To improve essential transformations, implementing CE must be simultaneously in the micro, meso, and macro systems (multi-level approach); this is necessary to help underscore the holistic, systemic change that CE requires. Furthermore, to SMEs, it is hard to visualize economic benefits as the implementation of CE practices often involves making extra investments that the SMEs may not consider profitable. Design/methodology/approach – We developed seven hypotheses and a theoretical model based on the literature review to answer the research question. The model and the hypotheses were tested according to the path analysis method, applying the model to a sample of 4,550 European SMEs. Our empirical analysis uses data from the Flash Eurobarometer 441 (European SMEs and the Circular Economy) and 2016 EUROSTAT database. Findings – The results support that the financial impact of adopting CE is positive, and it is affected by the level of national economic and environmental performance. Research Practical & Social implications – By connecting the emerging of CE to the national context, our study highlights the importance of considering the macro-level factors when analyzing the impact of CE adoption on firm performance. Public policies of direct investment, especially in countries with higher economic performance rates where firms operate at a higher level of competitiveness, can improve firm performance indicators and make CE adoption more attractive. Originality/value – Studies on CE exploration have a predominance of qualitative research with a single case; however, like CE is a practice-oriented paradigm, the use of quantitative methodology has become crucial to research articles in this field. This paper develop CE assessment frameworks and metrics at the country, industry, and firm levels with a quantitative method. Keywords – Circular Economy, Firm Performance, SMEs, multi-level